Kesesuaian areal budidaya rumput laut berdasarkan kapasitas perairan Desa Arakan Kabupeten Minahasa Selatan - Burase, Handy; Rompas, Robert; Ngangi, Edwin L.A. (Universitas Sam Ratulangi, 2013)
The purpose of this research was to provide data on waters physical and chemical parameters, proper areal map, carrying capacity, and potential production of seaweed. Research method used was spacial approach through direct measurement in the field and through laboratory analysis. Ten observation stations were established purposively at Desa Arakan waters. Samples were collected four times at two weeks interval. It was found that water temperature was 31–31,25 ºC, flow rate 5,97–11,09 cm/det., dissolved oxygen 5,34–6,45 mg/l, pH 7,7–8,1, salinity 32,5-33 ppt, nitrate 5,02–5,25 mg/l, phosphate 0,01–0,14 mg/l, water depth 1,3–16,5 m, velocity 1,3–4,5 m, tide 0–283 cm with Mean Sea Level 75,6 cm. bottom substrate consisted of coral sand and muddy sand. Proper culture area based on SIG analysis was 134.64 ha in which very proper areal was 68.40 ha, proper 66.23%. while proper areal was 66.23 ha. Based on carrying capacity analysis, proper sustainable site was 126.57 ha. This area could support 1.054 long line measuring 20x60 cm each. Seaweed potential was 3363,7 ton per ha or 4.4 ton/ha/year or 4.4 ton/ha/planting season. Keywords: marine seaweed, water quality, SIG, sea water, SIG, carrying capacity, production